PENGARUH PERPUTARAN PIUTANG DAN PERPUTARAN PERSEDIAAN TERHADAP TINGKAT RETURN ON ASSETS (ROA) PADA PT. NIPPON INDOSARI CORPINDO,TBK. - Wulandari, Nita; Hermuningsih, Sri; Prima Sari, Pristin (Universitas Veteran Bangun Nusantara, 2020)
The unstable level of net profit of PT. Nippon Indosari Corpindo and there are inconsistent research results on factors that affect profitability, the purpose of the study is to measure the influence of receivable turnover and inventory turnover on the profitability level of Return on Assets (ROA). This research uses purposive sampling method that is taking pt financial report data. Nippon Indosari Corpindo, Tbk. in the period 2010 – 2019 obtained from the Indonesia Stock Exchange (IDX). This research adopts a quantitative approach.The results of the study illustrated that partial turnover of receivables has no significant effect on profitability and then inventory turnover has a positive and significant influence on profitability. Simultaneously the turnover of receivables and inventory turnover have a significant effect on the level of profitability. Then in the coefficient of determination (R square) with a value of 0.843 which means 84.3% means that independent variables namely the turnover of receivables and inventory turnover has an influence of 84.3% on the level of Return on Assets (ROA), while the remaining 15.7% is explained by other factors that are not studied.Keywords: Receivable Turnover, Inventory Turnover, Profitability (ROA)